Geometric leaf classification - Kalyoncu, Cem; Toygar, Onsen (Academic Press Inc Elsevier Science, 2015)
In this paper, we propose a novel method including segmentation, a combination of new and well-known feature extraction and classification methods to classify plant leaves. The aim of the proposed features is to distinguish leaf margins, which cannot be distinguished using commonly used geometric features. Additionally, Linear Discriminant Classifier is used for classification, therefore using features that are noisy for some leaf types does not reduce the performance of the system. The proposed system outperforms the well-known geometric methods that are used for leaf classification. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Leaf classification; Geometric features; Linear Discriminant Classifier; Multi-scale distance matrix